COMPARATIVE ANALYSIS OF PAST TENSE VERBS IN ENGLISH AND ALBANIAN: A CASE STUDY OF THE NOVEL ‘THE OLD MAN AND THE SEA’ BY ERNEST HEMINGWAY AND ITS ALBANIAN VERSION ‘PLAKU DHE DETI’ - Erëza RUSHITI (Езиков свят, 2025)
This study investigates the use of past tense verbs in English and Albanian languages, using Hemingway’s novel “The Old Man and the Sea” and its Albanian version, “Plaku dhe Deti” by Ylber Pinjolli. Employing a qualitative approach, the research combines a descriptive method for the literature review and a comparative method for the analysis. Ten key instances of past tense verbs were selected from pivotal narrative moments to examine the past simple, past continuous, past perfect, and past perfect continuous tenses. The study explores how these grammatical structures shape the interpretation of temporal relationships and narrative coherence in both languages. The findings reveal significant differences in tense usage between the two texts. The Albanian translation often simplifies English tense structures, frequently substituting complex forms with the past simple tense. This approach, while maintaining narrative flow, sometimes reduces the precision and depth of temporal relationships expressed in the original. Furthermore, the limited use of the past perfect continuous tense in both versions highlights a gap in the Albanian tense system for depicting ongoing actions leading to specific past events. By analysing these variations, this study sheds light on the challenges of translating verb tenses across languages with distinct grammatical frameworks. It underscores the crucial role of tenses in literary translations and offers insights into how linguistic structures influence the preservation of narrative style and meaning.